Menimbang Ulang Program Makan Bergizi Gratis: Antara Kewajiban Negara dan Risiko Pelanggaran Hak Asasi Manusia - Raihan Muhammad (Jurnal Ilmu Hukum, 2026)
This article aims to analyze the problems of the Free Nutritious Meal Program (MBG) from a human rights perspective and to formulate policy reform directions aligned with the fulfillment of the right to food. This issue is significant because a program designed to improve nutritional status has revealed various implementation challenges, including food safety, nutritional quality, governance, and budgetary implications for other sectors. This study employs a normative juridical method with a qualitative approach by examining legal doctrines, scholarly literature, and empirical evidence derived from policy reports and findings. The results demonstrate that MBG continues to experience structural shortcomings in fulfilling the right to food, as reflected in weak oversight, unequal benefit distribution, limited public participation, and a policy orientation that prioritizes quantity over quality. Furthermore, the program’s budgetary policy has the potential to generate conflicts among the fulfillment of different rights, thereby failing to reflect an integrated rights-based approach. The novelty of this study lies in the development of an evaluation and policy reform model for MBG based on the Human Rights-Based Approach (HRBA), integrating the PANEL principles, the capability approach, and right-to-food-based evaluation indicators as a comprehensive framework for assessing and improving policy design and implementation. This reform model is expected to enhance policy effectiveness while ensuring the fulfillment of the right to food in a safe, adequate, equitable, and sustainable manner.